Pattern recognition : 41st DAGM German Conference, DAGM GCPR 2019, Dortmund, Germany, September 10-13, 2019, Proceedings /: 41st DAGM German Conference, DAGM GCPR 2019, Dortmund, Germany, September 10-13, 2019, Proceedings. (2019) - Unknown
No abstract available